2013
DOI: 10.3390/ijms141020983
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Matrix and Its Regulation in Pseudomonas aeruginosa

Abstract: Biofilms are communities of microorganisms embedded in extracellular polymeric substances (EPS) matrix. Bacteria in biofilms demonstrate distinct features from their free-living planktonic counterparts, such as different physiology and high resistance to immune system and antibiotics that render biofilm a source of chronic and persistent infections. A deeper understanding of biofilms will ultimately provide insights into the development of alternative treatment for biofilm infections. The opportunistic pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
233
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(243 citation statements)
references
References 130 publications
6
233
1
3
Order By: Relevance
“…We observed a fivefold decrease in the transcription of the cdrAB operon (Table 2), which not only confirmed the data generated using the cdrA-gfp reporter construct but also showed that doxorubicin is able to lower the expression of an adhesin important for biofilm formation (Borlee et al, 2010). Furthermore, it was found that doxorubicin lowered the transcription of genes encoding type IV pili, Cup fimbriae and LecA lectin (Table 2), which are all shown to play a role in biofilm formation by P. aeruginosa (Diggle et al, 2006;Giraud et al, 2011;Klausen et al, 2003;Wei & Ma, 2013). All genes that were up-or down-regulated more than twofold in the presence of doxorubicin are listed in Tables S1 and S2.…”
Section: Doxorubicin Does Not Impact Dgc Activity Of the Wspr Proteinsupporting
confidence: 72%
“…We observed a fivefold decrease in the transcription of the cdrAB operon (Table 2), which not only confirmed the data generated using the cdrA-gfp reporter construct but also showed that doxorubicin is able to lower the expression of an adhesin important for biofilm formation (Borlee et al, 2010). Furthermore, it was found that doxorubicin lowered the transcription of genes encoding type IV pili, Cup fimbriae and LecA lectin (Table 2), which are all shown to play a role in biofilm formation by P. aeruginosa (Diggle et al, 2006;Giraud et al, 2011;Klausen et al, 2003;Wei & Ma, 2013). All genes that were up-or down-regulated more than twofold in the presence of doxorubicin are listed in Tables S1 and S2.…”
Section: Doxorubicin Does Not Impact Dgc Activity Of the Wspr Proteinsupporting
confidence: 72%
“…With lower inactivation rates, however, bacterial populations were below detection limits after exposure to 120 s and 300 s of treatment. Similarly, Alkawareek et al 39 reported biphasic reductions of P. aeruginosa biofilms due to ACP treatment, where initial 60 s of plasma treatment resulted in rapid decline in bacterial levels, causing slower reduction between 60 s and 240 s of treatment. In general, our data suggest that 80kV air in-package DBD ACP treatment exhibits considerably high inactivation potential against the most abundant and resistant bacterial form-biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm studies to date, and in particular over the past 3 decades, have brought about extensive knowledge of the molecular details and functions of the multiple cellular elements involved in biofilm formation, including motility (47), surface behaviors (48), quorum sensing (49), and exopolysaccharide production (50). Yet, most studies to date have rarely accounted for fundamental features of the environment, in part due to the desire to focus on the simplest case in an already-complex problem, and in part due to experimental limitations in conventional approaches.…”
Section: A New Opportunity To Explore the Role Of A Dynamic Environmementioning
confidence: 99%